Visual thinking - Arnheim, Rudolf (Berkeley : University of California Press, 1997)
"This book is an attempt to proceed from earlier studies of art to a broader concern with visual perception as a cognitive activity ..."--Pref.
Early stirrings --The intelligence of perception --Two and two together --The past in the present --The images of thought --Concepts take shape --Pictures, symbols, and signs --What abstraction is not --What abstraction is --With feet on the ground --Thinking with pure shapes --Words in their place --Art and thought --Models for theory --Vision in education.
Includes bibliographical references (pages 325-338) and index.
Keywords: Visual perception; Art -- Philosophy